2009
DOI: 10.2165/00007256-200939080-00005
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Athletesʼ Stroke Volume Response to Progressive Exercise

Abstract: Untrained subjects typically demonstrate a plateau in stroke volume beyond the early stages of an acute bout of progressive exercise. Some studies have indicated that the stroke volume pattern in highly trained endurance athletes may differ, continuing to rise progressively to the point of maximal exercise. This suggests that the mechanism for generating cardiac output in these athletes may be influenced by cardiac functional factors, particularly augmented diastolic filling. This review of studies assessing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 68 publications
1
21
1
2
Order By: Relevance
“…9,22-24 Variations in these studies include a decrease, 25 a plateau 26 or an increase in SV when approaching volitional exhaustion 27 when untrained, moderately trained or heart disease patients are considered. 24 The prospective design and complexity of methods for measuring SV in most studies has generally limited sample sizes, and thus limited the external validity of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,22-24 Variations in these studies include a decrease, 25 a plateau 26 or an increase in SV when approaching volitional exhaustion 27 when untrained, moderately trained or heart disease patients are considered. 24 The prospective design and complexity of methods for measuring SV in most studies has generally limited sample sizes, and thus limited the external validity of the results.…”
Section: Discussionmentioning
confidence: 99%
“…The O 2 pulse has been demonstrated to be a powerful predictor of mortality in patients with cardiovascular diseases3,4 and it has been associated to the onset of exercise-induced ischemia 5,6. Although clinically useful, the O 2 pulse is not a simple variable to consider, since it is influenced by many factors that can confound its interpretation, including the presence of diastolic dysfunction,7 valvular regurgitation,8 fitness level (athletes may exhibit a plateau in oxygen pulse at higher levels of exercise, likely reflecting a physiological limitation of SV at the upper limits of HR),9 testing protocol10 and body dimensions 11. …”
Section: Introductionmentioning
confidence: 99%
“…twist; torsion; untwisting; diastole IN HEALTHY INDIVIDUALS, the increase in cardiac output at the transition from rest to exercise is achieved by a combination of both enhanced heart rate (HR) and stroke volume (SV) (18,21,25). Although some investigators have contested a plateau in SV during incremental exercise (14, 38), a considerable number of studies have shown that SV levels off at ϳ40 -50% of the maximal exercise capacity (18,21,22,25,26). This leveling off of SV is the result of a plateau in both end-diastolic volume (EDV) and end-systolic volume (ESV) (25).…”
mentioning
confidence: 99%
“…Although some investigators have contested a plateau in SV during incremental exercise (14,38), a considerable number of studies have shown that SV levels off at ϳ40 -50% of the maximal exercise capacity (18,21,22,25,26). This leveling off of SV is the result of a plateau in both end-diastolic volume (EDV) and end-systolic volume (ESV) (25).…”
mentioning
confidence: 99%
“…133 Second, the degree of volume load is also different. Endurance athletes commonly increase their SV by 20-40% at maximal work intensities, 125 while in severe chronic AR the extra volume entering the LV with each beat is more than 60 mL (or a near doubling of SV). 102 Although the eccentric hypertrophy seen in endurance exercise is generally attributed to intermittent increases in volume load during training sessions and competitions, there is also a ~10% blood volume expansion 27, 38, 131 which, in theory, could induce a slight chronic volume loading.…”
mentioning
confidence: 99%